Learning to Read: What We Know and What We Need to Understand Better - Hulme, C; Snowling, M (2013)
The authors review current knowledge about the cognitive processes underlying the early stages of word reading development. Recent findings in a variety of alphabetic languages converge on the conclusion that there are 3 "cognitive foundations" for learning to read: letter-sound knowledge, phonemic awareness, and rapid automatized naming skills. Deficits in each of these skills appear causally related to problems in learning to read, and deficits in letter-sound knowledge and phonemic awareness appear to be remediable by suitable teaching. The authors argue that this evidence has important practical implications for early education and for the diagnosis and treatment of children with reading difficulties. © 2012 The Authors. Child Development Perspectives © 2012 The Society for Research in Child Development.